2022
DOI: 10.1016/j.xkme.2022.100419
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Cysts in Hypophosphatemic Rickets With Hypercalciuria: A Case Series

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…As such, there is currently no published evidence to suggest that patients with hereditary forms of chronic phosphaturia, such as X-linked hypophosphatemic rickets, are at increased risk for developing CKD. However, a recent investigation in patients with hereditary hypophosphatemic rickets with hypercalciuria, a condition resulting in chronic urinary phosphate wasting, did find a high prevalence of kidney cyst formation in this patient population [38].…”
Section: Evidence For Phosphaturia and Phosphate-based Crystal Format...mentioning
confidence: 61%
“…As such, there is currently no published evidence to suggest that patients with hereditary forms of chronic phosphaturia, such as X-linked hypophosphatemic rickets, are at increased risk for developing CKD. However, a recent investigation in patients with hereditary hypophosphatemic rickets with hypercalciuria, a condition resulting in chronic urinary phosphate wasting, did find a high prevalence of kidney cyst formation in this patient population [38].…”
Section: Evidence For Phosphaturia and Phosphate-based Crystal Format...mentioning
confidence: 61%
“…3 A prior case series of 12 patients with SLC34A3 pathogenic variants (7 monoallelic, 5 biallelic) described a higher preponderance for kidney cysts than the general population. 6 SLC34A3 Ser192Leu heterozygotes had numerically more kidney/liver cyst ICD codes, although this was not statistically significant. Although we were limited by the lack of standardized laboratory testing, such as 24-hour kidney stone risk profiles, strengths of our study included a largely unselected cohort with long follow-up, allowing us to better capture nephrolithiasis burden.…”
mentioning
confidence: 75%
“…The primary outcome was nephrolithiasis; secondary outcomes included eGFR <60 ml/min per 1.73 m 2 , outpatient hypophosphatemia (lowest phosphate <2.5 mg/dl; median phosphate <3.0 mg/dl; meeting both criteria), mean phosphate, mean eGFR, and any kidney/liver cyst (ICD codes for autosomal dominant polycystic kidney disease, cystic kidney diseases, congenital kidney cyst, or liver cystic disease). 6,7 Chart reviews were performed by a nephrology fellow. EHR-based renal phenotypes were compared between SLC34A3 Ser192Leu heterozygotes and controls (without any SLC34A3 variants) using logistic and linear regression for categorical and continuous outcomes, respectively, adjusted for age, sex, and genetic ancestry and clustered by family network.…”
mentioning
confidence: 99%
“…Dasgupta et al reported that individuals with biallelic mutations in SLC34A3 alleles had an approximately tenfold higher risk of nephrolithiasis and nephrocalcinosis whereas heterozygotes had approximately 3-fold higher risk of nephrolithiasis (16.4%) compared with the general population (3). Another recent case series of 12 patients with SLC34A3 pathogenic variants (7 monoallelic, 5 biallelic) described a higher preponderance for kidney cysts than the general population (7). In our study SLC34A3 Ser192Leu heterozygotes had numerically more kidney/liver cyst ICD codes though this result was not statistically significant.…”
Section: Resultsmentioning
confidence: 99%